Social Networking to Support Collaborative Interactions in Special Education - Karagiannidis, Charalampos; Efraimidou, Sofia; Koumpis, Adamantios (International Journal of Emerging Technologies in Learning (iJET), 2010)
This paper proposes a framework for the collaboration of teachers in special education. The framework builds on, and extends, social networking services, in order to facilitate collaboration amongst the various categories of stakeholders. The innovation of our approach lies, according to our view, in providing a Service Model and a platform for social networking by using WS directly for the needs of the individual users. Although simple and efficient WS creation tools already exist, our idea is focused on allowing teachers to socially interact with each other -based on WS creation and use- and to create value for themselves and the community.